Maintenance management of aircraft component in component overhaul Department of Masa Sdn.Bhd / Mohd. Nor Azman Md. Zin and Anuar Abdullah Hashim - Md. Zin, Mohd. Nor Azman; Abdullah Hashim, Anuar (2000)
Over the past twenty years aircraft maintenance has changed more so than other maintenance management discipline. The changes are due to a huge increase in the number of aircraft types which must be maintained throughout the world, much more complex designs, new maintenance techniques and changing views of maintenance organization and responsibilities. Aircraft maintenance is also responding to changing expectations. These include a rapidly growing awareness of the extent to which component failures affects safety and other consequences the environment, a growing awareness of the connection between maintenance and product quality and increasing pressure to achieve high plant availability and to contain costs.